Stopping Power and Range for Proton Interaction with Lymph Tissues - Shaima M. Hadi (Three E Science Institute, 2021)
In this paper, we calculated the mass stopping power (in MeV cm2/g) and the range (cm) of proton in one of the types of body tissues (lymph), from 1 Kev to 200 MeV energy range. They are using the Bethe and Ziegler equations, SRIM program (version 2013) and Ziegler (Vol. 3) data by considering the tissue composed of several elements, so the atomic number (Z) and atomic weight (A) for the component in the tissue are meaning. The calculation results show that the Ziegler equation gives better results than using the Bethe equation. However, in terms of the loss of proton energy in the tissue, the four methods used are approximately the same.